Costos de producción de banano orgánico de la finca Clelia Irlanda en la zona de Pasaje durante el periodo 2000-2005 - Sotomayor Sánchez, Dario Javier (2007)
The present work was carried out in the Clelia Ireland farm to deter-mine the production cost of organic banana from its started as one in 2000 to 2005. The objectives were: 1. Determine the production cost in the Clelia Ireland farm during the period 2000 – 2005. 2. Identify the economic profitability derived of the organic banana production. 3. Analyze the positive impact derived of the organic production from human point of view. The production costs in the Clelia Ireland farm changed from its start-ed, due the inversion, above all with the infrastructure, the plantation sustenance respect the workers wages, various according the increase or diminution of the price in organic banana box abroad, and so on. It was determined the 30 boxes production per hectare according the price abroad let to obtain better ingresses between 32 % and 43% in positive forms respect to the production cost, with the exception of the first starter year and the first production years, Where the cost isn’t take as one, but is an inversion of 67 % and 13 % recoverable in short time and in comparison with the banana’s traditional box abroad the organic surpass in 55 % and 87 %. That mean the economic profitabil-ity is positive, due the production costs diminish significantly in the second year, then start to increase, but it doesn’t affect in negative form the ingresses for the box price increase abroad. The priority an organic certification is the human capital, for what feeding, study and clothing are taken as one in the Clelia Ireland farm, besides the correct and opportune application of products let guarantee a quality fruit.